2003
DOI: 10.1152/jn.00064.2003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of the Timing and Tuning of Visual-Related, Saccade-Related, and Delay Period Activity in Primate Central Thalamus

Abstract: This study investigates the visuomotor properties of several nuclei within primate central thalamus. These nuclei, which might be considered components of an oculomotor thalamus (OcTh), are found within and at the borders of the internal medullary lamina. These nuclei have extensive anatomical links to numerous cortical and subcortical visuomotor areas including the frontal eye fields, supplementary eye fields, prefrontal cortex, posterior parietal cortex, caudate, and substantia nigra pars reticulata. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
110
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(126 citation statements)
references
References 76 publications
16
110
0
Order By: Relevance
“…The location of cylinder was somewhat anterior to the previous studies that used rhesus monkeys [1][2][3][4] , since the stereotaxic coordinates of the motor thalamus extend more anteriorly in Japanese monkeys 5 . Animals received analgesia with either suppository acetaminophen or intramuscular injection of pentazocine after each surgery.…”
Section: Animal Preparationmentioning
confidence: 87%
See 2 more Smart Citations
“…The location of cylinder was somewhat anterior to the previous studies that used rhesus monkeys [1][2][3][4] , since the stereotaxic coordinates of the motor thalamus extend more anteriorly in Japanese monkeys 5 . Animals received analgesia with either suppository acetaminophen or intramuscular injection of pentazocine after each surgery.…”
Section: Animal Preparationmentioning
confidence: 87%
“…Since previous studies show no clear topography of eye movement signals in the ventrolateral thalamus 2,6 , the peripheral target was placed either 12° right or left of the central fixation throughout the experiments. In both the visually-guided saccade task and the externally triggered memory-guided task, monkeys were required to make a saccade within 400 ms after the offset of the fixation target (Supplementary Fig.…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Projections from the contralateral superior colliculus may hereby cross at tectal and thalamic levels (27,28). Indeed, electrophysiological work in primates indicates that corollary discharge-related activity at the thalamic level represents both ipsi-and contralateral saccades and eye positions (17,29). Patient studies using a double-step task noted contra-and bilateral impairments with thalamic lesions but also strictly ipsilateral deficits in several cases (14,30).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that neurons in the central thalamus carried eye movement signals that were related to saccades, fixation, and eye or gaze position in space Schalg-Rey, 1984, 1986;Goldman-Rakic, 2003, 2004;Wyder et al, 2003;Sommer and Wurtz, 2004a;Watanabe and Funahashi, 2004). However, it remains unknown whether the central thalamus also transmits signals that are related to smooth pursuit eye movements.…”
Section: Introductionmentioning
confidence: 99%